2020
DOI: 10.1101/2020.09.01.278283
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feature-based encoding of face identity by single neurons in the human amygdala and hippocampus

Abstract: Neurons in the human medial temporal lobe (MTL) that are selective for the identity of specific people are classically thought to encode identity invariant to visual features. However, it remains largely unknown how visual information from higher visual cortex is translated into a semantic representation of an individual person. Here, we show that some MTL neurons are selective to multiple different face identities on the basis of shared features that form clusters in the representation of a deep neural networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(94 citation statements)
references
References 38 publications
14
64
0
Order By: Relevance
“…Furthermore, we observed similar results using the entire neuronal population ( n = 490, permutation P = 0.003; amygdala neurons: n = 242, permutation P = 0.12; hippocampal neurons: n = 248, permutation P < 0.001). Although identity neurons (i.e., neurons that selectively encoded certain identities) (Cao et al 2020b) might enhance the correlation between face identities, we derived similar results when we excluded identity neurons ( n = 57, permutation P = 0.004). Lastly, we derived similar results when we constructed DMs using face images instead of face identities ( Figure S2 ; all permutation Ps < 0.008).…”
Section: Resultssupporting
confidence: 53%
“…Furthermore, we observed similar results using the entire neuronal population ( n = 490, permutation P = 0.003; amygdala neurons: n = 242, permutation P = 0.12; hippocampal neurons: n = 248, permutation P < 0.001). Although identity neurons (i.e., neurons that selectively encoded certain identities) (Cao et al 2020b) might enhance the correlation between face identities, we derived similar results when we excluded identity neurons ( n = 57, permutation P = 0.004). Lastly, we derived similar results when we constructed DMs using face images instead of face identities ( Figure S2 ; all permutation Ps < 0.008).…”
Section: Resultssupporting
confidence: 53%
“…Such difference in function between the amygdala and hippocampus is consistent with our previous finding showing that only the amygdala but not the hippocampus encode perceived facial emotions (Wang et al 2014). However, the amygdala and hippocampus play a similar role in encoding face identities (Cao et al 2020), visual selectivity (Kreiman et al 2000, Wang et al 2018), memory (Rutishauser et al 2010), and visual attention (Wang et al 2018). Furthermore, although some faces in the CelebA stimuli have facial expressions (because the celebrities posed when taking the photos) and eye movement can be biased by facial expressions (Scheller et al 2012), we observed similar results in an unpublished study using emotionally neutral FaceGen model faces.…”
Section: Discussionmentioning
confidence: 99%
“…Only units with an average firing rate of at least 0.15 Hz (entire task) were considered (Cao et al 2020). Fixations were aligned to fixation onset and saccades were aligned to saccade onset.…”
Section: Methodsmentioning
confidence: 99%
“…The present study continues from our recent work showing feature-based encoding of face identities in the human MTL using DNN-extracted visual features [24] (an encoding-related study). The motivation for the present study is largely two-fold.…”
Section: Introductionmentioning
confidence: 62%
“…Patients performed a one-back task (Fig. 5A; accuracy = 75.7±5.28% [mean±SD across sessions]) and they could well recognize the faces [24]. The responses of 46/490 neurons (9.39%) differed between different face identities in a window 250-1000 ms following stimulus onset and these neurons were the real human identityselective neurons.…”
Section: Establishing the Relationship Between Artificial Dnn Neurons And Real Human Neuronsmentioning
confidence: 99%